2020
DOI: 10.1177/1462474520925159
|View full text |Cite
|
Sign up to set email alerts
|

“Discipline that hurts”: Punitive logics and governance in sport

Abstract: In this paper, we undertake a case study of the National Hockey League’s supplementary discipline regime to reflect on the ways in which discourses about social harm are configured, taken up and used in the sporting landscape and how they reflect and reify narrow understandings of crime and punishment. We find that the hockey world employs predictable crime and justice metaphors when discussing on-ice violence and suggest this breeds fear and legitimates governance strategies. The National Hockey League’s supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…This could have downstream impacts on reductions of violence against more generally. However, it is also important to note that leagues and organizations sanctioning players after a violent arrest does nothing to change many of the underlying professional sport structures that promote violence, aggression, dominance and in the case of the NFL, brain injury (Kennedy and Silva, 2020; Messerschmidt and Connell, 2005), all of which are important factors in explaining continued off-field violence by athletes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could have downstream impacts on reductions of violence against more generally. However, it is also important to note that leagues and organizations sanctioning players after a violent arrest does nothing to change many of the underlying professional sport structures that promote violence, aggression, dominance and in the case of the NFL, brain injury (Kennedy and Silva, 2020; Messerschmidt and Connell, 2005), all of which are important factors in explaining continued off-field violence by athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining media coverage of off-field athlete violence has found that the men accused (and especially Black men accused) are framed and pathologized as naturally aggressive (Enck-Wanzer, 2009). Athlete violent behaviour is also blamed on the few 'bad apples' involved, rather than interrogating sport leagues and larger sporting culture's complicity (Anderson, 2017;Kennedy and Silva, 2020). This is consistent with Raymen and Smith's (2019) description of the leisure and sport space as privileging the 'individualism of the autonomous subject, protected by negative liberty' which, combined 'with the competitive individualism of consumer capitalism, cultivate(s) subjectivities willing to harm others in the pursuit of their own desires ' (p. 122).…”
Section: Physical Violence and Organizational Deviance In Sportmentioning
confidence: 99%
See 2 more Smart Citations
“…My analysis was conducted using critical discourse analysis (CDA), which many criminologists have used to highlight how relations of power are sustained through 'language-in-use', or language as used to interact and communicate (Kennedy & Silva, 2020;Van Dijk, 2011). CDA has a particular focus on highlighting the impact of language use (Gee, 2011, in Tight, 2019.…”
Section: Methodsmentioning
confidence: 99%